Hard of hearing as a presenting complaint in patients with chronic otitis media - Hubballi, Ravi Kishore; Koripalli, Keerthi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media (COM) is highly prevalent disease of middle ear. Common presenting complaint is ear discharge. Though pathogenesis of COM involves alteration of conductive mechanism of hearing, it has been observed that hard of hearing (HOH) is not the presenting complaint in all cases of COM. Therefore, this study is taken up to know prevalence of hard of hearing as a presenting complaint in patients with COM. Methods: 100 patients were taken up for study. Detailed history and examination were done. The samples were assessed based on gender, age, presenting complaints, duration between onset of ear discharge and HOH and the type of hearing loss. Results: Out of 100 patients with COM, HOH was presenting complaint in 60%. Ear discharge was most common complaint. In 10% HOH was the only complaint. Among 40% who did not complain of HOH, 24% gave history of HOH and 16% patients denied any history of HOH. Conclusions: Though pathogenesis of COM involves alteration of conductive mechanism of hearing but yet not all patients of COM present with or give history of HOH. In COM as the disease process advances slowly, the patient appears to adapt to the loss so that thresholds of 30-40 dB HL are common with little complaint from the patient. Our present study indicated that among 100 patients, 84 patients presented with or gave history of HOH and 16 patients did not have presenting complaint or history of HOH but those 16 patients were proved to be having conductive hearing loss on examination.